Enhancing Product Modelling Process Design and Visual Performance Through Random Forest Optimization - Cheng, Xin; He, Hua (Informatica, 2024)
The design cycle's crucial component of manufacturing process optimization includes issue formulation, modeling, simulations, optimization, and deployment. Simulation methodologies are essential to get actual optimization rather than just process improvements. This study proposes a random forest approach for analyzing and optimizing product aesthetics and integrating new technology into design. Virtual display technology lets customers see product performance in detail, making buying easier. Virtual display technology improves user experience and product sales. We use a machine learning technique called random forest to handle complex data and make reliable predictions. We analyze and optimize product aesthetics using design components, material choices, and consumer preferences. Virtual display technology helps us incorporate new technologies into the design. We tried the random forest approach for analyzing and optimizing product aesthetics and virtual display technology. Our results show that random forest forecasts and optimizations increase product attractiveness.. This study emphasizes industrial process optimization and simulation's role in actual optimization. We offer a random forest approach for analyzing and optimizing product aesthetics and integrating new technology into design. Virtual display technology improves software capabilities and gives users a complete understanding of product performance. The outcomes of the proposed system has provided 95% accuracy, 94% precision and 98% recall which enhance process effectiveness and user experience.